Case Report: Tumor Microenvironment Characteristics in a Patient With HER2 Mutant Lung Squamous Cell Carcinoma Harboring High PD-L1 Expression Who Presented Hyperprogressive Disease - Xia, Lixia; Yu, Yinghui; Lan, Fen; Yan, Junrong; Li, Jinfan; Li, Wen; Xia, Yang (Frontiers in Oncology, 2021)
Background: High PD-L1 expression in non-small cell lung cancer (NSCLC) is evident to predict elevated immunotherapy efficacy, to which NSCLC with onco-driver genes mutations is probed with poor responsiveness. Thus, it is of great interest to investigate how effective immune monotherapy is in the presence of concurrent high PD-L1 expression and driving genes mutation. Patients and methods: We present a case of squamous lung cancer with high PD-L1 expression and HER2 exon 20 insertion (20Ins) who presented hyperprogressive disease (HPD) after being treated with PD-1 inhibitor. Results: A 71-year-old female was diagnosed with advanced squamous lung cancer with 98% tumor proportion score of PD-1 and 20ins. She benefited from first-line docetaxel cisplatin followed by 2 months second-line afatinib. Third-line pembrolizumab monotherapy was then given. Unfortunately, she rapidly progressed with dramatically enlarged primary site as well as mediastinal lymph nodes and pleural effusion only 2 weeks later, presenting severe dyspnea and dysphagia. Re-biopsy was conducted and we found that compared with the baseline, CD8+ T cells were largely recruited only in tumor stroma but not in tumor parenchyma. Tumor associated macrophages were notably increased in both tumor stroma and parenchyma. Concomitantly, CD56dim NK cells in tumor parenchyma were decreased. Conclusions: Application of immune monotherapy in patients with positive driver genes demands extreme caution, even harboring high PD-L1 expression. Abnormality of tumor microenvirnoment might be critically involved in immune checkpoint inhibitors induced HPD. Further study in greater depth is required.